PENGARUH MODAL INTELEKTUAL DAN PENGUNGKAPAN LAPORAN KEBERLANJUTAN TERHADAP PROFITABILITAS (Studi pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Periode 2014-2016) - Sri Wulandari Martiningsih; Willy Sri Yuliandhari (Universitas Widyatama, 2018)
Companies listed on the Indonesia Stock Exchange are companies that need funds from investors so that stakeholders have an important role in the sustainability of the company. companies must make returns on investments made by investors so that companies do various ways to increase profits. Profitability ratios can be used to measure profits that can be obtained by the company. The purpose of this study to analyze the factors that are considered to affect the company's profitability include intellectual capital calculated using the VAICTM formula and disclosure of sustainability reports calculated using the IndexSR formula based on the GRI-G4 Sustainability Report Guidelines. The sample in this study were 19 companies listed on the Indonesia Stock Exchange for the 2014-2016 period. The method used in this study is descriptive statistics and panel data regression. The sample selection technique used is purposive sampling. Data analysis method uses panel data regression analysis with a significance level of 5%. Based on the results of the study, simultaneous intellectual capital and disclosure of sustainability reports have a significant effect on company profitability of 31.4701%. Partially, intellectual capital has a significant positive effect on profitability while disclosure of sustainability reports does not affect profitability.